La implementación de los programas de estudio de Matemática en primaria desde la visión de la persona docente - Hidalgo Mora, Randall (2022)
The objective of this paper is to analyze, from the perspectives of elementary school teachers, the processes they carry out in their classrooms in terms of methodologies and evaluations used in the development of programs for the study of mathematics. A mixed approach was used in the study, which was based on a sequential design. Non-probabilistic sampling was used for convenience. In the first phase of the research, 117 elementary school teachers from schools in Costa Rica were surveyed. In the second phase, interviews were conducted with three teachers. A questionnaire was used to collect data, and semi-structured interviews were also carried out. The results obtained show that implementation of the Mathematics curriculum led to methodological changes and adjustments in the process of evaluation among the teaching staff, but also created problems. In general, the blackboard was the most used resource, but the use of additional tools has diversified. There is little use of technology and discussion of the history of mathematics as teaching resources. Knowledge of the curriculum is not adequate; priority is given to content, rather than to the development of skills. The teaching staff has difficulty in planning and developing problem-solving activities. Teachers should participate in continuous training processes in areas including mathematical knowledge, methodological and evaluation strategies, use of technology, and problem solving.